Multi-omics Investigation of Freeze Tolerance in the Amur Sleeper, an Aquatic Ectothermic Vertebrate. (20th February 2023) - Jiang, Haifeng; Lv, Wenqi; Wang, Ying; Qian, Yuting; Wang, Cheng; Sun, Ning; Fang, Chengchi; Irwin, David M; Gan, Xiaoni; He, Shunping; Yang, Liandong
Abstract: Freeze tolerance, the ability of an organism to survive internal ice formation, is a striking survival strategy employed by some ectotherms living in cold environments. However, the genetic bases of this remarkable adaptation are largely unknown. The Amur sleeper ( Perccottus glenii ), the only known freeze-tolerant fish species, can overwinter with its entire body frozen in ice. Here, we sequenced the chromosome-level genome of the Amur sleeper and performed comparative genomic, transcriptomic, and metabolomic analyses to investigate its strategies for surviving freezing. Evolutionary analysis suggested that the Amur sleeper diverged from its closest non-cold-hardy relative about 15.07 million years ago and has experienced a high rate of protein evolution. Transcriptomic and metabolomic data identified a coordinated and tissue-specific regulation of genes and metabolites involved in hypometabolism, cellular stress response, and cryoprotectant accumulation involved in freezing and thawing. Several genes show evidence of accelerated protein sequence evolution or family size expansion were found as adaptive responses to freezing-induced stresses. Specifically, genetic changes associated with cytoskeleton stability, cryoprotectant synthesis, transmembrane transport, and neuroprotective adaptations were identified as potentially key innovations that aid in freezing survival. Our work provides valuable resources and opportunities to unveil the molecular adaptations supporting freeze tolerance in ectothermic vertebrates.